INJURY DISTRIBUTION ON AUTOPSY IN CASES OF FATAL CRANIO-CEREBRAL INJURIES: AN EXPERIENCE FROM RURAL CENTRAL INDIA (Journal of Forensic Medicine & Toxicology, 2011)
The present study focuses the types and pattern of intracranial hemorrhages in fatal cranio-cerebral injuries and associated injuries sustained to the victims in rural areas. The present study deals with the autopsy findings of the fatal cases of cranio-cerebral injuries occurring in the rural parts of Central India. The present study was carried out at Mahatma Gandhi Institute of Medical Sciences, Sevagram, District-Wardha during the period of October 2002 to September 2004. 150 consecutive cases of fatal cranio-cerebral injuries were included in present study. The occurrence of associated injuries in trauma patients is not uncommon, and the associated injuries include as head trauma, chest injury, abdominal trauma, pelvic injury or fracture, upper limb fracture, lower limb fracture. Head injuries are the major accidental injury and one of the commonest causes in young people and the most important is the fact that these injuries are potentially preventable. It has been suggested that prevention of the head injuries and treatable injuries elsewhere in the body might have saved many lives and as a health professional and policy makers we need to recognize this growing problem as a public health crisis and design appropriate policy responses.
Keywords: Postmortem; Trauma; Fatal vehicular accidents; Fracture; Head injury; Road accidents; Pattern of injuries; Distribution of injuries; Autopsy